System of Equations. Gary has 4 boxes of fruit and 2 pounds of pineapple. Susie has 3 boxes of fruit and 3 pounds of pineapple. What would the weight.

Slides:



Advertisements
Similar presentations
Solving Equations = 4x – 5(6x – 10) -132 = 4x – 30x = -26x = -26x 7 = x.
Advertisements

Making an Equation from a Table (Option 2) By: Mrs. Waters.
System of Equations Keyona Nettles. LOGO Slogan.
JEOPARDY Click here and type Category 1 Click here and type Category 2 Click here and type Category 2 Click here and type Category 3 Click here and type.
Algebra 1: Solving Equations with variables on BOTH sides.
3.5 Solving systems of equations in 3 variables
Write and graph a direct variation equation
1 Integrated Mathematics Solving Exponential Equations.
Substitute 0 for y. Write original equation. To find the x- intercept, substitute 0 for y and solve for x. SOLUTION Find the x- intercept and the y- intercept.
Substitute 0 for y. Write original equation. To find the x- intercept, substitute 0 for y and solve for x. SOLUTION Find the x- intercept and the y- intercept.
1 Integrated Mathematics Solving Exponential Equations.
Parabola Quiz 10 Revision questions. Write the equation for this parabola #1.
Click to Begin Click to Begin. Solving Multi-step Equations Vocabulary Simplifying Algebraic Expressions Solving One and Two One and Two Step Equations.
Equations Reducible to Quadratic
Substitution Method: 1. Solve the following system of equations by substitution. Step 1 is already completed. Step 2:Substitute x+3 into 2 nd equation.
Type your question here. Type Answer Type your question here. Type Answer.
3.6 Solving Absolute Value Equations and Inequalities
STUDENTS WILL BE ABLE TO: CONVERT BETWEEN EXPONENT AND LOG FORMS SOLVE LOG EQUATIONS OF FORM LOG B Y=X FOR B, Y, AND X LOGARITHMIC FUNCTIONS.
EXAMPLE 1 Find a positive slope Let (x 1, y 1 ) = (–4, 2) = (x 2, y 2 ) = (2, 6). m = y 2 – y 1 x 2 – x 1 6 – 2 2 – (–4) = = = Simplify. Substitute.
Solving by Elimination Example 1: STEP 2: Look for opposite terms. STEP 1: Write both equations in Standard Form to line up like variables. STEP 5: Solve.
Section 5.3 Solving Systems of Equations Using the Elimination Method There are two methods to solve systems of equations: The Substitution Method The.
SECONDARY ONE 6.1a Using Substitution to Solve a System.
7.3 Solving Systems of Equations The Elimination Method.
Y=3x+1 y 5x + 2 =13 Solution: (, ) Solve: Do you have an equation already solved for y or x?
The Substitution Method Objectives: To solve a system of equations by substituting for a variable.
Warm-Up 1) Determine whether (-1,7) is a solution of the system. 4 minutes 3x – y = -10 2) Solve for x where 5x + 3(2x – 1) = 5. -x + y = 8.
Notes 6.5, Date__________ (Substitution). To solve using Substitution: 1.Solve one equation for one variable (choose the variable with a coefficient of.
Algebra Review. Systems of Equations Review: Substitution Linear Combination 2 Methods to Solve:
SOLVING SYSTEMS OF EQUATIONS BY SUBSTITUTION PRACTICE PROBLEMS.
Quiz Title Your name goes here. Question 1 Click here for answer Click here for answer Go to question 2 Go to question 2.
Insert your name and class period here. 1. What is the goal of every equation you solve? 2. How do we accomplish this goal? Type your answer here.
SOL 4.22 Demonstrating the Meaning of Equality. Now Lets Review What We Just Learned.
7.3 Solving Equations Using Quadratic Techniques
Equations Quadratic in form factorable equations
Solve Systems of Equations by Elimination
Mathsercise-C Ready? Inequalities Here we go!.
Three Types of Percent Problems
Lesson 111: Three Statements of Equality
Solve an equation by multiplying by a reciprocal
Click here for the answer. Click here for the answer.
Click here for the answer. Click here for the answer.
Copyright 2011 Davitily.
Click here for the answer. Click here for the answer.
Integrated Mathematics
Warm-Up Solve the system by substitution..
Learn to solve whole-number division equations.
Solve a system of linear equation in two variables
3.5 Solving systems of equations in 3 variables
Solving Two-Step Equations
Let {image} Use substitution to determine which elements of S satisfy the inequality {image} Select the correct answer(s): {image}
Simultaneous Equations substitution.
Solving One and Two Step Equations
Solving One Step Equations
10/10/ Bell Work Write and answer the following questions.
Quadratic Systems. What you’ll learn
Click here for the answer. Click here for the answer.
Tables and Relations Review
Refresh: Click Here.
Equations Quadratic in form factorable equations
5.2 Substitution Try this one: x = 4y y = 5x 4x – y = 75 2x + 3y = 34
Simultaneous Equations
Solving Systems of Equations By Substitution
Use the ten frames to help solve the problems
4 minutes Warm-Up 1) Determine whether (-1,7) is a solution of the system. 3x – y = -10 -x + y = 8 2) Solve for x where 5x + 3(2x – 1) = 5.
On your whiteboards: Solve this equation 4a + 5 = 29 4a = 24 a = 6.
X ⦁ X = 64 ±8 ±14 X ⦁ X ⦁ X =
Indicator 16 System of Equations.
(Type Answer Here) (Type Answer Here) (Type Answer Here)
Solving Linear Equations
Presentation transcript:

System of Equations

Gary has 4 boxes of fruit and 2 pounds of pineapple. Susie has 3 boxes of fruit and 3 pounds of pineapple. What would the weight be of each box of fruit if both Gary and Susie had the same total weight of fruit? Define our variablesy: total weight x: boxes of fruit

Gary has 4 boxes of fruit and 2 pounds of pineapple. Susie has 3 boxes of fruit and 3 pounds of pineapple. What would the weight be of each box of fruit if both Gary and Susie had the same total weight of fruit? Gary’s total = Susie’s total 4x + 2 = 3x + 3 Gary y=4x+2 Susie y=3x+3

Let’s solve for x 4x + 2 = 3x + 3

Both Gary and Susie have 6 pounds Gary y=4x+2Susie y=3x+3 Substitute x = 1 and solve for the total.

Solve this system: y=4x+2y=3x+3

y = 2x + 9 y = 5x – 3 x= 4, y = 17 (4, 17) y = 7x – 15 y = 3x + 5 x = 5, y = 20 (5, 20) click here for answer 1.2. click here for answer

y=–5x+14x–y=10 x – (–5x + 14) = 10

y = 2x – 1 5x – 2y = 4 x= 2, y = 3 (2, 3) x = –y x – 3y = 15 x = 9, y = 1 (9, 1) click here for answer 3.4.

y = x y = 2x + 1 x= –1, y = –1 (–1, –1) y = x + 7 x + y = 35 x = 14, y = 21 (14, 21) click here for answer 5.6.

y = 3x x + 2y = –21 x = –3, y = –9 (–3, –9) y = 3x – 8 y = 4 – x x = 3, y = 1 (3, 1) click here for answer 7.8.